2022
DOI: 10.1108/jbim-10-2020-0484
|View full text |Cite
|
Sign up to set email alerts
|

Does the type of sales position matter? A multi-group analysis of inside vs outside sales

Abstract: Purpose This study aims to investigate the differences between inside and outside business-to-business salespeople. Although prior research has highlighted a need to compare these two distinct sales positions, limited research examines the two. Specifically, this study investigates differences between inside and outside salespeople for the following constructs: positivity, intrinsic and extrinsic motivation, emotional exhaustion, job satisfaction and turnover intentions. Design/methodology/approach A Qualtri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
(170 reference statements)
0
4
0
Order By: Relevance
“…Although this research included a diverse sample, respondents tended to be older, well-educated males; therefore, future research may want to expand the demographics of the sample to enhance generalizability. Further, this study did not distinguish between inside and outside salespeople as indicated in Matthews and Edmondson (2022) which should be considered as a potential moderator in the future. This study uses cross-sectional data; therefore, a longitudinal study could also prove insightful.…”
Section: Limitations and Future Researchmentioning
confidence: 79%
See 2 more Smart Citations
“…Although this research included a diverse sample, respondents tended to be older, well-educated males; therefore, future research may want to expand the demographics of the sample to enhance generalizability. Further, this study did not distinguish between inside and outside salespeople as indicated in Matthews and Edmondson (2022) which should be considered as a potential moderator in the future. This study uses cross-sectional data; therefore, a longitudinal study could also prove insightful.…”
Section: Limitations and Future Researchmentioning
confidence: 79%
“…When salespeople are excited about their work, they are less likely to feel exhausted. Organizations can increase emotional engagement by hiring empathetic managers, recognizing and acknowledging salespeople’s contributions, encouraging diversity, incorporating beneficial sales coaching and providing authentic and transparent lines of open communication, A variety of other ways that organizations can help reduce emotional exhaustion of their salespeople can be found in Edmondson et al (2019) and Matthews and Edmondson (2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the first studies have established the conceptual grounding for inside sales by distinguishing its key configurations and outlining some of the capability requirements for applying these configurations (Sleep et al , 2020), this research has largely studied the phenomenon without paying any attention to the specificities of its different configurations (Chaker et al , 2022; Homburg et al , 2021; Matthews and Edmondson, 2022; Ohiomah et al , 2019). Thus, the extant research on specific inside sales configurations and their management remains almost nonexistent.…”
Section: Conceptual Backgroundmentioning
confidence: 99%